Effect of Fu Zheng Jie Du Formula on outcomes in patients with severe pneumonia receiving prone ventilation: a retrospective cohort study - Cai, Hairong; Luo, Sicong; Cai, Xingui; Lai, Ting; Zhao, Shuai; Zhang, Weizhang; Zhuang, Jieqin; Li, Zhishang; Chen, Li; Chen, Bojun; Ye, Ye (Frontiers in Pharmacology, 2024)
The effect of combining prone ventilation with traditional Chinese medicine on severe pneumonia remains unclear.Objective: To evaluate the effect of Fu Zheng Jie Du Formula (FZJDF) combined with prone ventilation on clinical outcomes in patients with severe pneumonia.: This single-center retrospective cohort study included 188 severe pneumonia patients admitted to the ICU from January 2022 to December 2023. Patients were divided into an FZJD group (receiving FZJDF for 7 days plus prone ventilation) and a non-FZJD group (prone ventilation only). Propensity score matching (PSM) was performed to balance baseline characteristics. The primary outcome was the change in PaO2/FiO2 ratio after treatment. Secondary outcomes included 28-day mortality, duration of mechanical ventilation, length of ICU stay, PaCO2, lactic acid levels, APACHE II score, SOFA score, Chinese Medicine Score, inflammatory markers, and time to symptom resolution.Results: After PSM, 32 patients were included in each group. Compared to the non-FZJD group, the FZJD group showed significantly higher PaO2/FiO2 ratios, lower PaCO2, and lower lactic acid levels after treatment (P<0.05 for all). The FZJD group also had significantly lower APACHE II scores, SOFA scores, Chinese Medicine Scores, and levels of WBC, PCT, hs-CRP, and IL-6 (P<0.05 for all). Time to symptom resolution, including duration of mechanical ventilation, length of ICU stay, time to fever resolution, time to cough resolution, and time to resolution of pulmonary rales, was significantly shorter in the FZJD group (P<0.05 for all). There was no significant difference in 28-day mortality between the two groups.Conclusions: FZJDF as an adjuvant therapy to prone ventilation can improve oxygenation and other clinical outcomes in severe pneumonia patients. Prospective studies are warranted to validate these findings.